Inhibition of Small Conductance Calcium-Activated Potassium (SK) Channels Prevents Arrhythmias in Rat Atria During β-Adrenergic and Muscarinic Receptor Activation - Skibsbye, Lasse; Bengaard, Anne K.; Uldum-Nielsen, A. M.; Boddum, Kim; Christ, Torsten; Jespersen, Thomas (Frontiers in Physiology, 2018)
Sympathetic and vagal activation is linked to atrial arrhythmogenesis. Here we investigated the SK-channel pore-blocker N-(pyridin-2-yl)-4-(pyridin-2-yl)thiazol-2-amine (ICA) on action potential (AP) and atrial fibrillation (AF) parameters in isolated rat-atria during β-adrenergic (isoprenaline) and muscarinic M2 (carbachol) activation. Furthermore, Antiarrhythmic efficacy of ICA was benchmarked towards the class-IC antiarrhythmic drug flecainide. Isoprenaline increased the spontaneous beating frequency but did not affect other AP parameters. As expected, carbachol hyperpolarized resting membrane potential (-6.2±0.9 mV), shortened APD90 (24.2±1.6 vs. 17.7±1.1 ms) and ERP (20.0±1.3 vs. 15.8±1.3 ms). The duration of burst-pacing triggered AF was unchanged in the presence of carbachol compared to control atria (12.8±5.3 vs. 11.2±3.6 s), while β-adrenergic activation resulted in shorter AF durations (3.3±1.7 s) and lower AF-frequency compared to carbachol. Treatment with ICA (10 µM) in isoprenaline-stimulated atria prolonged APD90 and ERP, while the AF burden was reduced (7.1±5.5 vs. 0.1±0.1 s). In carbachol-stimulated atria, ICA treatment also resulted in APD90 and ERP prolongation and shorter AF durations. Flecainide treatment in carbachol-stimulated atria prolonged APD90 and ERP and abbreviated the AF duration to a similar extent as with ICA. Muscarinic activated atria constitutes a more arrhythmogenic substrate than β-adrenoceptor activated atria. Pharmacological inhibition of SK channels by ICA is effective under both conditions and equally efficacious to flecainide.